2010
DOI: 10.1007/s10646-010-0476-1
|View full text |Cite
|
Sign up to set email alerts
|

Acute, subacute, and subchronic exposure to 2A-DNT (2-amino-4,6-dinitrotoluene) in the northern bobwhite (Colinus virginianus)

Abstract: 2-Amino-4,6-dinitrotoluene (2A-DNT) is a metabolite of the explosive 2,4,6-trinitrotoluene (TNT) which is present in the soil at numerous U.S. Army installations as the result of TNT manufacture or training activities. Although many avian species are known to inhabit areas where 2A-DNT has been found in the environment, no published studies of the effects of 2A-DNT exposure in birds are available. In this study, we conducted an evaluation of the oral toxicity of 2A-DNT in a representative ground foraging speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Quinn et al [4] conducted an evaluation of the oral toxicity of 2A-DNT in the Northern Bobwhite (Colinus virginianus). Subacute (14 days) and subchronic (60 days) oral gavage exposure studies were conducted following determination of the median acute lethal dose (LD 50 ¼ 1,167 mg/kg).…”
Section: Summary Of Avian Toxicologymentioning
confidence: 99%
See 1 more Smart Citation
“…Quinn et al [4] conducted an evaluation of the oral toxicity of 2A-DNT in the Northern Bobwhite (Colinus virginianus). Subacute (14 days) and subchronic (60 days) oral gavage exposure studies were conducted following determination of the median acute lethal dose (LD 50 ¼ 1,167 mg/kg).…”
Section: Summary Of Avian Toxicologymentioning
confidence: 99%
“…Only one study that assessed the toxicity of 2A-DNT following ingestion in birds [4] could be located (see Table 16.4). The approximation approach is required for TRV derivation as the data do not fit the minimum data requirements of TG 254 [1] since the study is subchronic and is the only study available for this taxonomic class.…”
Section: Toxicity Reference Values For Birdsmentioning
confidence: 99%
“…Wildlife bird species represent important potential receptors of MCs, especially ground foraging birds that may inadvertently consume these chemicals when ingesting grit or soils to assist with digestion [ 5 ]. Quinn et al [ 6 ] examined the toxicological effects of 2A-DNT in the ground foraging bird species, Northern bobwhite ( Colinus virginianus ), and found that it was acutely toxic only at high doses (LD 50 = 1167 mg/kg). However, in subchronic 60d exposures, sustained oral dosing of 2A-DNT was observed to elicit mortality at a much lower dose (14 mg/kg-d, [ 6 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Quinn et al [ 6 ] examined the toxicological effects of 2A-DNT in the ground foraging bird species, Northern bobwhite ( Colinus virginianus ), and found that it was acutely toxic only at high doses (LD 50 = 1167 mg/kg). However, in subchronic 60d exposures, sustained oral dosing of 2A-DNT was observed to elicit mortality at a much lower dose (14 mg/kg-d, [ 6 ]). In addition to mortality, 2A-DNT dosing caused a variety of sublethal effects in the subchronic exposures including: increased liver weights, decreased leukocyte counts, increased plasma-triglyceride levels and splenic reticular cell hyperplasia [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation